The Relationship Between Math Learning Anxiety, Time Management Ability, and Emotional Support with Academic Achievement of Junior High School Students in Indonesia - Maghfiroh, Nasruliyah Hikmatul; Hanurawan, Fattah; Hitipeuw, Imanuel (West Science Interdisciplinary Studies, 2024)
This research explores the relationship between anxiety over math learning, the ability of time management, and emotional support on students' academic achievement among junior high school students in Indonesia. The data collected from 120 participants is assessed within a quantitative research design where surveys were administered using the 1-5 Likert scale. The tool to be used for analysis is known as structural equation modeling, partial least square-PLS3. The results indicated that math learning anxiety negatively impacts academic achievement, while time management ability and emotional support facilitate improvement in academic achievement. Both time management ability and emotional support act as mediators in the relationship between math learning anxiety and academic performance. These results highlight the need to reduce anxiety, develop time management skills, and build emotional support to improve students' academic performance. The study provides actionable insights for educators, parents, and policymakers in providing a supportive educational environment that ensures holistic student development.